Analysis of the Amendment of the Content of Crimes that endanger the Integrity and Sexual Freedom of Minors, the Recruitment of Minors for Sexual Purposes in the New Regulation of Law no 217/2020: Array - Ionescu Dumitrache, Ana Alina (Acta Universitatis Danubius. Juridica, 2020)
This article highlights the main changes in the content of crimes against the integrity and sexual freedom of minors, changes made by Law no. 217/2020 for the amendment and completion of Law no. 286/2009 on the Criminal Code, as well as for the amendment of art. 223 para. (2) of Law no. 135/2010 on the Code of Criminal Procedure. It is also analyzed, in detail, with the presentation of examples from judicial practice, the crime of recruiting minors for sexual purposes.